Exploring the Challenges towards Active Learning at a Public University in Afghanistan: A Case Study of EFL Lecturers’ Perceptions - Tareen, Hashmatullah (Pacific International Journal, 2022)
Active learning is often connected with teaching and learning that is progressive and involves active student participation. The chief purpose of this research project was to explore Afghan EFL lecturers’ perceptions towards challenges hampering active learning. With regards to achieving this objective, a qualitative research approach, in particular, face-to-face interviews were conducted. The researcher interviewed and collected the data from seven EFL lecturers in the Languages and Literature Faculty and EFL lecturers in Education Faculty at Kandahar University. This study identified large classes, lack of technological facilities, lack of time, shortage of lecturers, and cultural issues as the challenges hampering active learning.